2021
DOI: 10.1002/dc.24756
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intra‐observer and inter‐observer variability of pathologists for non‐benign thyroid fine needle aspiration cytology according to Bethesda system categories

Abstract: AimTo examine the intra‐ and inter‐observer variability for non‐benign thyroid cytological subcategories according to the Bethesda classification system after the second review.MethodsBetween November 2018 and May 2019, thyroid fine needle aspiration biopsies of 381 nodules were retrospectively evaluated. Among them, 74 non‐benign (category III‐VI) thyroid biopsies, analyzed according to the Bethesda system (pathologist 1:40 vs pathologist 2:34) by two independent pathologists, were reassessed by the same path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…Firstly, we demonstrated that the overall FNAC results according to the Italian thyroid cytology system were significantly different between the two centers: indeed, as already noted in some studies according to other internationally recognized systems for reporting thyroid cytology ( 20 , 21 ), we observed that the cytopathologists of the HV center tended to score lower the benign nodules and higher those with final diagnosis of malignancy. Perhaps, this was due to the extensive expertise of our thyroid cytopathologists to more easily detect both the benign and malignant cases, compared with operators that work in LV services where thyroid FNAC occupies only a small place in the daily routine.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Firstly, we demonstrated that the overall FNAC results according to the Italian thyroid cytology system were significantly different between the two centers: indeed, as already noted in some studies according to other internationally recognized systems for reporting thyroid cytology ( 20 , 21 ), we observed that the cytopathologists of the HV center tended to score lower the benign nodules and higher those with final diagnosis of malignancy. Perhaps, this was due to the extensive expertise of our thyroid cytopathologists to more easily detect both the benign and malignant cases, compared with operators that work in LV services where thyroid FNAC occupies only a small place in the daily routine.…”
Section: Discussionsupporting
confidence: 62%
“…However, to our knowledge, limited literature exists on the evaluation of the inter-observer variability of the cytological diagnosis of thyroid nodules according to the three main classification systems (i.e., Bethesda, RCPath, ICCRTC) ( 20 29 ). Moreover, few studies were based on raters from institutions with different expertise and case load ( 21 , 29 ).…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, RoM suffers from wide interinstitutional and interobserver variability, particularly for specimens that fall into the morphologically indeterminate TBS categories: III (atypia of undetermined significance [AUS]), IV (follicular neoplasm or suspicious for follicular neoplasm [SFN), and V (suspicious for malignancy [SUS]). [3][4][5][6][7] In addition, because only a subset of indeterminate thyroid nodules undergo surgical resection, assessment of the RoM is challenging. Beyond the RoM, the only recommendation that the first (2010) edition of TBS made regarding secondary QA metrics was for most practice settings to use an interim goal for the frequency of AUS interpretations of approximately 7% of all thyroid fine-needle aspiration (FNA) diagnoses.…”
Section: Introductionmentioning
confidence: 99%
“…The RoM is particularly important because it serves both as an indicator of clinical actionability and as the principal quality‐assurance (QA) metric for individual pathologists and pathology laboratories that use TBS. Unfortunately, RoM suffers from wide interinstitutional and interobserver variability, particularly for specimens that fall into the morphologically indeterminate TBS categories: III ( atypia of undetermined significance [AUS]), IV ( follicular neoplasm or suspicious for follicular neoplasm [SFN), and V ( suspicious for malignancy [SUS]) 3‐7 . In addition, because only a subset of indeterminate thyroid nodules undergo surgical resection, assessment of the RoM is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…As cytological diagnosis is a more qualitative or subjective mode of interpretation than it is a quantitative analysis, there is a possibility of inter- and intra-observer variation among cytologists’ interpretations [ 50 , 56 ]. For example, even though the Paris system (TPS) was established to standardize the cytological interpretation of urine samples, there are still many conflicting opinions about the criteria for some categories.…”
Section: Discussionmentioning
confidence: 99%